The development of young peoples’ internalising and externalising difficulties over the first three-years in the public care system - Hiller, Rachel M. (Child maltreatment, 2023)
Although we know there are high rates of mental health difficulties amongst young people in out-of-home care (i.e. social welfare-involved children), there is limited evidence on the longitudinal development of these problems, particularly from when they enter the care system. Using the routinely collected carer-reported strengths and difficulties questionnaire, we explored internalising (emotional and peer) and externalising (conduct and hyperactivity) difficulties for 672 young people across their first 3 years in the UK care system (2?16 yrs, 51% boys, 76% Caucasian). In all cases stable profiles (resilient or chronic) were most common, while changing profiles (recovery or delayed) were less common. Findings showed that entry into the care system is not enough of an intervention to expect natural recovery from mental health difficulties. Number of placements and being separated from siblings were associated with greater difficulties. Implications for child welfare and mental health systems are discussed.